A novel cancer testis antigen target A-kinase anchor protein (AKAP4) for the early diagnosis and immunotherapy of colon cancer. (1st February 2016) - Jagadish, Nirmala; Parashar, Deepak; Gupta, Namita; Agarwal, Sumit; Sharma, Aditi; Fatima, Rukhsar; Suri, Vaishali; Kumar, Rajive; Gupta, Anju; Lohiya, Nirmal Kumar; Suri, Anil
ABSTRACT: Colorectal cancer (CRC) is mainly a disease of developed countries and a major cause of death worldwide. The present study was undertaken to investigate the association of novel cancer testis (CT) antigen, A-kinase anchor protein (AKAP4) with CRC. AKAP4 gene and protein was examined by RT-PCR, in situ hybridization and immunohistochemistry (IHC) in 200 clinical specimens of different stages and grades. In addition, humoral response against AKAP4 was detected by enzyme-linked immunosorbent assay and Western blotting in 172 available sera samples of CRC patients. We observed that majority of CRC patients demonstrated AKAP4 expression and elicited immune response. AKAP4 protein expression, based on immunoreactivity score (IRS) predicted presence of CRC with 84% sensitivity, 100% specificity, 100% of positive predictive value (PPV) and 83.33% negative predictive value (NPV). Humoral response against AKAP4 protein was generated in 82% of the CRC patients. Further, statistical analysis revealed that antibodies found against AKAP4 in CRC patients predicted presence of malignancy with 81.98% sensitivity, 100% specificity, 100% PPV, and 63.53% NPV. Collectively, our data suggests that the majority of CRC cases show significant difference of AKAP4 expression among stages and grades and also generated antibodies against AKAP4 protein. Therefore, AKAP4 may be potential candidate molecule for developing as a biomarker for early diagnosis and immunotherapy of CRC.